Analisis wacana kritis film the accountant: Special value akuntan forensik pengidap autistik - Rafles Ginting; David Crystopher; Khristina Yunita (Jurusan Akuntansi,Fakultas Bisnis dan Ekonomika,Universitas Surabaya, 2024)
This study aims to reveal the relationship between autistic behavior and the basic characteristics that forensic accountants need to have. This research uses a critical discourse analysis method. Critical discourse analysis was carried out on the research object of the film